Disparities in HIV‐1 transmitted drug resistance detected by ultradeep sequencing between men who have sex with men and heterosexual populations. Issue 9 (26th April 2017) - Todesco, E; Charpentier, C; Bertine, M; Wirden, M; Storto, A; Desire, N; Grude, M; Nguyen, T; Sayon, S; Yazdanpanah, Y; Katlama, C; Descamps, D; et al.
Abstract : Objectives: Transmitted drug resistance (TDR) can impair the response to first‐line antiretroviral therapy. In treatment‐naïve patients chronically infected with HIV type 1 (HIV‐1), it was previously shown through Sanger sequencing that TDR was more common in men who have sex with men (MSM) than in other transmission risk groups. We aimed to compare two HIV‐1 transmission groups in terms of the presence of TDR mutations. Methods: We investigated, through Sanger sequencing and ultradeep sequencing (UDS), the presence of resistance mutations, both in majority (> 20%) and in minority (1−20%) proportions, in 70 treatment‐naïve MSM and 70 treatment‐naïve heterosexual patients who recently screened positive for HIV‐1. Results: The global prevalence of TDR was not significantly different between the two groups, either by Sanger or by UDS. Nevertheless, a higher frequency of nucleoside reverse transcriptase inhibitor TDR was observed among heterosexual patients ( P = 0.04). There was also a trend for a higher frequency of TDR among MSM infected with HIV‐1 subtype B compared with MSM infected with HIV‐1 non‐B subtypes ( P = 0.06). Conclusions: Ultradeep sequencing UDS allowed sensitive monitoring of TDR, and highlighted some disparities between transmission groups.